2021
DOI: 10.1073/pnas.2016648118
|View full text |Cite
|
Sign up to set email alerts
|

A conserved long noncoding RNA, GAPLINC, modulates the immune response during endotoxic shock

Abstract: Recent studies have identified thousands of long noncoding RNAs (lncRNAs) in mammalian genomes that regulate gene expression in different biological processes. Although lncRNAs have been identified in a variety of immune cells and implicated in immune response, the biological function and mechanism of the majority remain unexplored, especially in sepsis. Here, we identify a role for a lncRNA—gastric adenocarcinoma predictive long intergenic noncoding RNA (GAPLINC)—previously characterized for its role in cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…The limited primary sequence conservation of lncRNAs between humans and rodents (Roux et al, 2017) could be a major obstacle in this context. Among the few immune-regulatory lncRNAs found to be conserved between humans and mice, so far, are CARLR, IL7-AS and GAPLINC, which regulate pro-inflammatory cytokine production (Castellanos-Rubio et al, 2017;Roux et al, 2017;Vollmers et al, 2021). An important task for the future will be to identify further locus-or structure conserved orthologues and functional equivalents of human immune-regulatory lncRNAs in mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The limited primary sequence conservation of lncRNAs between humans and rodents (Roux et al, 2017) could be a major obstacle in this context. Among the few immune-regulatory lncRNAs found to be conserved between humans and mice, so far, are CARLR, IL7-AS and GAPLINC, which regulate pro-inflammatory cytokine production (Castellanos-Rubio et al, 2017;Roux et al, 2017;Vollmers et al, 2021). An important task for the future will be to identify further locus-or structure conserved orthologues and functional equivalents of human immune-regulatory lncRNAs in mice.…”
Section: Discussionmentioning
confidence: 99%
“…GAPLINC deficiency enhanced baseline expression of NFκB dependent genes in human cells and mice. This pre-activation of immune-response genes protected GAPLINC-deficient mice from LPS-induced endotoxin shock-a fulminant inflammatory response syndrome, associated with high mortality (Vollmers et al, 2021). Other examples of lncRNAs suppressing premature immune responses, which are downregulated upon bacterial PAMP-stimulation, are lincRNA-EPS (Atianand et al, 2016) and lnc13 in murine phagocytes.…”
Section: Positive Control Of Nfκb Driven Immunity Upon Prr-activationmentioning
confidence: 98%
See 1 more Smart Citation
“…Subsequently, GAPLINC was found to be highly expressed in hepatocellular carcinoma (44) and non-small-cell lung cancer (45) and was found to promote cancer through different mechanisms. Vollmers et al found that GAPLINC knockout mice showed resistance to endotoxic shock induced by lipopolysaccharide (46). At the same time, Mo and other studies have shown that GAPLINC can promote the tumor-like biological behavior offibroblast-like synoviocytes in patients with rheumatoid arthritis through a ceRNA mechanism (47).…”
Section: Quantitative Analysis Of the Abundance Of Mirnas And Targetmentioning
confidence: 96%
“…Several lines of evidence have shown that lncRNAs are capable of influencing different cellular functions that are critical to tumorigenesis, such as cell proliferation, differentiation, migration, immune response, and apoptosis [41][42][43][44][45][46][47]. Furthermore, lncRNAs have been found to act as tumor suppressors or oncogenes [48][49][50][51], and, of note, a number of lncRNAs have been reported to be significantly deregulated in tumors [52][53][54][55].…”
Section: Long Non-coding Rna Structures and Functionsmentioning
confidence: 99%